A Green, One-Pot Formation of Imidazolone and Pyrimidinone Derivatives Containing a Sulfonyl Group. (November 2016) - Nematpour, Manijeh; Koohi, Samira Rasouli; Abedi, Elahe; Lotfi, Mahbob
The synthesis of sulfonyl-imidazolone derivatives via a four-component reaction between sodium arylsulfinates, trichloroacetonitrile, benzylamines and acetylenedicarboxylates in H2 O at room temperature is described. When alkyl propiolate was used instead of acetylenedicarboxylates, sulfonyl-pyrimidinone was obtained.